2023
DOI: 10.3390/math11143064
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Soil Compaction Parameters Using an Enhanced Hybrid Intelligence Paradigm of ANFIS and Improved Grey Wolf Optimiser

Abstract: The criteria for measuring soil compaction parameters, such as optimum moisture content and maximum dry density, play an important role in construction projects. On construction sites, base/sub-base soils are compacted at the optimal moisture content to achieve the desirable level of compaction, generally between 95% and 98% of the maximum dry density. The present technique of determining compaction parameters in the laboratory is a time-consuming task. This study proposes an improved hybrid intelligence parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Stepping beyond traditional ANNs, a novel hybrid intelligence paradigm known as the ANFIS-IGWO model was proposed in a different study. This model demonstrated superior precision in predicting soil compaction parameters, boasting correlation values of 0.9203 and 0.9050 for w opt and ρ dmax , respectively [29]. This accuracy was found to surpass other hybrid ANFIS models.…”
Section: Introductionmentioning
confidence: 82%
“…Stepping beyond traditional ANNs, a novel hybrid intelligence paradigm known as the ANFIS-IGWO model was proposed in a different study. This model demonstrated superior precision in predicting soil compaction parameters, boasting correlation values of 0.9203 and 0.9050 for w opt and ρ dmax , respectively [29]. This accuracy was found to surpass other hybrid ANFIS models.…”
Section: Introductionmentioning
confidence: 82%
“…Building upon these traditional approaches, advanced AI methodologies have brought significant advancements in the fields of geotechnical characterization in cohesive soils. Comparative analyses have been conducted on various machine learning models and soft computing techniques to predict key soil properties such as soil compaction parameters [60]- [62], shear strength properties [63]- [67] and the suitable percentage of waste materials for soil improvement [68]. In these studies, the proposed models showed superior performance with high prediction accuracy.…”
Section: F Research Frontier Identificationmentioning
confidence: 99%
“…Wolves with lesser responsibilities are positioned at the lower ranks of the pack hierarchy. The hunting procedure in GWO may be categorized as searching, surrounding, hunting, and attacking (Bardhan et al, 2023). They exhibit several solutions and continuously adjust the locations of these wolves according to their tness function values.…”
Section: Optimization Algorithmmentioning
confidence: 99%